Enhancing Arabic Speaking Proficiency (Maharah al-Kalam) through the Implementation of Problem-Based Learning - Isnani, Nur Athifah; Wahyudin, Wahyudin; Syahid, Akhmad (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The speaking ability (Maharah al-Kalam) of students at State Islamic Senior High School 3 Makassar remains relatively low, primarily due to limited innovation in teaching methods and the minimal active participation of learners in classroom activities. This study aims to examine the implementation of Problem-Based Learning (PBL) as an alternative instructional model to address these challenges and enhance students’ proficiency in Arabic speaking skills. Employing a Classroom Action Research (CAR) design, the study involved 31 students of class X.6 as research participants. Data collection instruments included classroom observations, teacher and student interviews, and an oral performance test consisting of five questions administered both at the beginning and end of the cycles. The findings revealed a significant improvement in students’ Arabic speaking ability across the two research cycles. The average score increased from 62.35% in the pre-cycle to 74.90% in cycle I, and further improved to 93.12% in cycle II. These results demonstrate that PBL not only promotes active participation and collaborative learning but also significantly enhances oral proficiency in Arabic. The study contributes to the field of Arabic language pedagogy by providing empirical evidence of the effectiveness of PBL in improving Maharah al-Kalam within Islamic senior high school contexts.